Proposal of Sociocultural Indicators of Sustainability Applicable to Goat Producers in Northwestern Córdoba, Province of Córdoba, Argentina - Pen, Cecilia Valeria; Brouard Uriburu, María del Rosario; Villar, Martha Beatriz; Rodríguez Maiztegui, Miguel Angel; Acuña, Narda Isabel; Romero, Claudia del Huerto; Durando, Patricia Evelina (Agrociencia Uruguay, 2019)
In this paper, sociocultural indicators of sustainability were applied to small goat breeder’s productive systems of Cruz del Eje and Rio Seco departments (Córdoba province, Argentina). Such indicators (established for dairy cattle systems and adapted to goat raising systems) were: A- General Participation: level of participation in collective spaces. B- Productive Participation: joint management of goods. C-Training: productive and non-productive training in the last three years. D-Subjective Life Quality: acceptability of the production system as a way of life. E- Structural Life Quality: living place, transport, basic and health services. F- Continuity: age of the person in charge of the establishment. To characterize the level of sociocultural sustainability of goat farmers, interviews were performed (n=41), using such indicators. The sociocultural sustainability index was calculated for each producer. Such index enabled the classification of the productive establishments in three levels of sustainability: high, medium or low. The multivariate statistical analysis allowed to state that General Participation, Productive Participation, Training, Subjective Life Quality, and Continuity were positively correlated, and also explained the high level of sustainability. The indicator Structural Life Quality was correlated with the low sustainability of the productive system. In conclusion, the selected sociocultural indicators and indices resulted adequate to characterize the sustainability level of the productive systems dedicated to goat production in northwestern Córdoba.